Effect of Developmental Care to Decrease Stress Hospitalization in Low Birth Weight Baby in NICU - W, Pipit Festi; Wintarti, Reni; Husna, Anis Rosyiatul (Jurnal Keperawatan Muhammadiyah, 2018)
Stress hospitalization is often experienced by low birth weight (LBW) infants who are experiencing nurses in the hospital. Developmental care is one developmental care developed in order to minimize the impact of hospitalization. This study aims to deter- mine the effect of developmental care on hospitalization stress reduction among LBW infants in NICU Dr. Moh Soewandhi Hospital. Pre-experimental Design One Group Pre-Post Test Design was used. 30 respondents obtained by using Simple Random Sampling technique. The independent variable was development care and the depen- dent variable was stress hospitalization. Developmental care procedure checklist and the behavior sheet of LBW infant instrument were used. The data was analyzed using Wilcoxon Signed Rank Test with significance level Î± = 0.05. The results showed that almost half (46.7%) of respondents had moderate stress before Development Care was done, and most of them (73.3%) did not experience stress after Development Care. The Wilcoxon Signed Rank Test analysis showed that p = 0,000 at significance level Î± = 0.05. It means that there is influence of developmental care to decrease stress of hospi- talization on LBW Infant in NICU Dr Moh Soewandhi Hospital. In sum, develop- ment Care can reduce hospitalization stress in LBW. Therefore, it is suggested that the whole family to do Development Care on LBW who experience stress hospitalization.